2008
DOI: 10.1245/s10434-008-0178-6
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions Following Pancreaticoduodenectomy for Pancreas Cancer: A Population-Based Appraisal

Abstract: Procedure complexity and volume-outcome relationships have led to increased regionalization of pancreaticoduodenectomy (PD) for pancreas cancer. Knowledge regarding outcomes after PD comes from single-institutional series, which may be limited if a significant number of patients follow up at other hospitals. Thus, readmission data may be underreported. This study utilizes a population-based data set to examine readmission data following PD. California Cancer Registry (1994-2003) was linked to the California's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 21 publications
8
107
2
Order By: Relevance
“…There is a recent report about a high rate of re-admission after PD (n=2,023 resections, re-admission rate after 30 days-59%). 26 These are sobering results and raise important questions about the provision of specialized services at high and low volume centers and the necessity for audit of results for review and improvement in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is a recent report about a high rate of re-admission after PD (n=2,023 resections, re-admission rate after 30 days-59%). 26 These are sobering results and raise important questions about the provision of specialized services at high and low volume centers and the necessity for audit of results for review and improvement in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown the contrary, i.e., elderly patients have a higher mortality rate, have a tendency to stay longer in the intensive care unit, have higher incidences of postoperative cardiac events, experience more nutritional and functional difficulties, and show a higher rate of readmission compared to younger patients (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…6 Prior studies have found that between 20% and 28% of patients who underwent surgical cancer treatment were readmitted to a different hospital. 7,8 One study found that approximately 15% of patients with colon cancer who underwent colectomy were readmitted within 30 days. Of those, 17% were readmitted to a different hospital from the index hospital.…”
Section: Resultsmentioning
confidence: 99%